PERGERESERAN FUNGSI KELUARGA DALAM IKLAN IMOO WATCH PHONE Z6 - Nugroho, Rendi Adi (Paradigma, 2021)
Family is the first institution experienced by every individual. This institution can be a family with blood relations or a family without blood relations. Television shapes various social realities. One of them is family life. Families are one of the targets of advertising companies that are used as target markets as well as promotional materials. But one item that is usually not advertised with a family background is a watch. One watch ad that takes place in a family setting is the IMOO Watch Phone. The role of a watch in this advertisement gives a feeling of reassuring for parents or in other words entrusting their children to this sophisticated watch. This is due to one of the features that provide surveillance via cameras such as the CCTV function. This study aims to explain the shift in family functions, the role of technology and the reality of a new form of family in the IMOO Watch Phone Z6 advertisement. This study uses a qualitative method using the Charles Sanders Pierce Semiotics approach. And using Robert K Merton's theory of Family Sociology as an analytical knife. The results showed that the family is the most important role holder in the process of socializing values and norms in shaping the child's personality so that they are ready to enter the social world. The presence of new technologies such as communication tools makes it easier for parents to socialize values and norms through pictures, videos, to voice messages. The existence of the Watch Phone is an alternative choice for parents in the middle and upper economy as an answer to the problem of limited time between busy work and the functions of family institutions. Watch Phone advertisements depict a family in the middle and upper economy interacting with a group of game friends using a Watch Phone. In the midst of busy parents in carrying out their work, the presence of a Watch Phone can help parents monitor their children's activities outside the home. Keywords: Family Function, Semiotics, Technology, IMOO Watch Phone